Hydrophobic high-CTI high-strength polyphenylene sulfide composite material and preparation method thereof
By adding modified montmorillonite, reactive silicone oil and coupling agent to the polyphenylene sulfide composite material, and performing twin-screw extrusion and irradiation treatment, the problem of insufficient CTI value of the existing polyphenylene sulfide composite material is solved, and a composite material with a high CTI value of more than 600V and high strength is achieved.
Patent Information
- Application Number
- CN202411917829.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
AI Technical Summary
The leakage trace index (CTI) value of existing polyphenylene sulfide composite materials has not yet reached 600V, making it difficult to meet the areas of anti-fouling, anti-corrosion and high CTI requirements.
By mixing polyphenylene sulfide, modified montmorillonite, reactive silicone oil, coupling agent and lubricant evenly, double screw extrusion is carried out, combined with carbonization inhibitor and chopped glass fiber feed, melt blending and extrusion granulation is carried out, and polyphenylene sulfide composite material with high CTI high strength is prepared by irradiation treatment.
The high CTI value of composite materials is achieved exceeding 600V, combining high strength and good hydrophobicity, and is suitable for areas with anti-fouling and corrosion protection and high CTI requirements.
Abstract
Description
Technical Field Technical Field
[0001] The invention relates to the field of polymer modification, and in particular to a hydrophobic high CTI high-strength polyphenylene sulfide composite material and a preparation method thereof. Background Art
[0002] Polyphenylene sulfide has excellent dielectric properties, flame retardancy, high heat resistance, high dimensional stability, and chemical resistance, and is widely used in the fields of electronics, automobiles, aerospace, etc. Polyphenylene sulfide contains a large number of benzene rings and is easy to form carbon, so the tracking index is low, generally below 150V, which limits its scope of use.
[0003] Patent number CN 112457670 B discloses a hydrophobic high CTI polyphenylene sulfide composition and its preparation method. The compatibility of PPS and glass fiber materials is improved by coupling agents, and the rigidity and toughness of the materials are further improved. At the same time, by adding fluorosilicone oil, the low surface energy and super hydrophobic characteristics of fluorosilicone oil are utilized. During the injection molding process, the low surface energy will be accumulated on the surface of the material, which has little effect on the rigidity of the material. At the same time, after the fluorosilicone oil is accumulated on the surface, the super hydrophobic characteristics will greatly reduce the wetting of the electrolyte on PPS, which can significantly improve the CTI of the PPS material. The CTI value of the PPS composite material obtained by this patent is about 250V. Patent number CN 117903596 A discloses a high CTI polyphenylene sulfide composition based on multi-dimensional formula design, preparation method and application. The material is composed of the following components in weight percentage: PPS resin 10.5-89.96%; glass fiber 10-50%; filler mineral 0.01-30%, gallium oxyhydroxyl 0.01-5%, silane-modified epoxy resin 0.01-1.5%; stabilizer 0.01-3%. The CTI value can be increased by using silane-modified epoxy resin to increase the hydrophobicity of the material, special plastic fillers to block PPS from becoming a continuous phase, and other methods. The CTI value can reach 500V. The CTI values of the above patents have not yet reached 600V. Patent No. CN 117186643 B discloses a polyphenylene sulfide composite material with an ultra-high relative tracking index and a preparation method thereof, which is mainly composed of the following raw materials in parts by weight: 30 to 50 parts of PPS resin, 40 to 60 parts of filler, 0.5 to 2 parts of antioxidant, and 3 to 8 parts of toughening agent; the filler is mainly composed of chopped glass fiber and at least one of mica powder, boron nitride nanosheets, boron nitride whiskers, silicon nitride whiskers, nanoporous silica, nano silicon carbide, nano α-alumina, nano zirconium oxide, and tungsten disulfide; the filler is treated with a surface modifier, and the mass ratio of the filler to the surface modifier is (0.8 to 1.2):(98.8 to 99.2); the surface modifier is mainly composed of a fluorosilicone surface treatment agent and methacryloxysilane in a mass ratio of (8 to 25):(75 to 92); the fluorosilicone surface treatment agent is mainly made of vinyl silane and fluorine-containing acrylate. This patent only considers the hydrophobic treatment of the filler, but does not consider the hydrophobic modification of PPS to improve the CTI value of the composite material. Summary of the invention
[0004] In view of the above problems, the present invention proposes a preparation method of a hydrophobic high CTI high-strength polyphenylene sulfide composite material, which is suitable for fields with high CTI requirements for antifouling and anticorrosion. Polyphenylene sulfide, modified montmorillonite, reactive silicone oil, coupling agent, and lubricant are mixed evenly and then put into the main feed of a twin-screw extruder, and carbonization inhibitor and short chopped glass fiber are added from different side feeds, melt blended, extruded and granulated, and then irradiated to obtain a polyphenylene sulfide composite material with high CTI and high strength.
[0005] A hydrophobic high CTI high-strength polyphenylene sulfide composite material, calculated by weight, the raw material composition includes: Polyphenylene sulfide: 20-50 Glass fiber: 20-50 Coupling agent: 0.2-2 Carbonization inhibitor: 20-40 Modified montmorillonite: 5-12 Reactive silicone oil: 0.2-6 Lubricant: 0.5-2.
[0006] The polyphenylene sulfide is a linear polyphenylene sulfide having a melt index of 200-1500 g / 10 min when tested at 316° C. and 5 kg.
[0007] The glass fiber is alkali-free chopped glass fiber with a length of 2-6 mm and a diameter of 7-13 μm.
[0008] The coupling agent is one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent, or a mixture of several of them.
[0009] The carbonization inhibitor is one or a mixture of magnesium hydroxide, aluminum hydroxide, zinc borate and calcium borate.
[0010] The modified montmorillonite is sodium-based montmorillonite grafted with a silane coupling agent.
[0011] The reactive silicone oil is one of epoxy silicone oil, carboxyl silicone oil and amino silicone oil, or a mixture of several of them.
[0012] The lubricant is one of silicone, tetrapentyl stearate and montan wax or a mixture of several of them.
[0013] The above materials except glass fiber and carbonization inhibitor are mixed uniformly, and then put into the main feeding loss-in-weight scale of the twin-screw extruder, the glass fiber is added to the first side feeding loss-in-weight scale, and the carbonization inhibitor is added to the second side feeding loss-in-weight scale, melt blended and then extruded, and polyphenylene sulfide composite material particles are obtained after cooling and pelletizing, and then the particles are irradiated to finally obtain a high CTI and high-strength polyphenylene sulfide composite material.
[0014] Preferably, the coupling agent is a silane coupling agent.
[0015] Preferably, the reactive silicone oil is amino silicone oil.
[0016] Preferably, the carbonization inhibitor is magnesium hydroxide.
[0017] Preferably, the lubricant is silicone.
[0018] Under the above preferred conditions, the hydrophobic glass fiber reinforced polyphenylene sulfide composite material preferably comprises, by weight, the raw material composition: Polyphenylene sulfide: 20-40 Glass fiber: 20-50 Silane coupling agent: 0.2-1 Magnesium hydroxide: 20-35 Montmorillonite: 6-10 Amino silicone oil: 2-4 Silicone: 1-1.5 In addition, the present invention also provides a method for preparing a hydrophobic high CTI reinforced polyphenylene sulfide, comprising the following steps: (1) Preparation of modified montmorillonite. Weigh KH-560 and montmorillonite in a mass ratio of 4:5 respectively for use. First, add KH-560 to an ethanol solution prepared with acetic acid to a pH of 4 and hydrolyze for 4 hours. Then, add montmorillonite to the mixed solution and reflux at 70°C for 24 hours. Then, dilute the product with anhydrous ethanol, wash, and filter to obtain modified montmorillonite.
[0019] (2) The modified montmorillonite obtained in step 1 is mixed with polyphenylene sulfide, silane coupling agent, amino silicone oil and silicone, and then put into the main feed loss-in-weight scale of a co-rotating twin-screw extruder with a length-to-diameter ratio of 52:1, the glass fiber is put into the side feed loss-in-weight scale of the 6th section, and the magnesium hydroxide is put into the side feed loss-in-weight scale of the 10th section. The mixture is heated and melted for extrusion, and the reinforced polyphenylene sulfide composite material is obtained after air cooling and pelletizing. The mixture is melt extruded at 280-320°C.
[0020] (3) The obtained reinforced polyphenylene sulfide is subjected to electron beam or gamma ray irradiation treatment to obtain a hydrophobic, high CTI, and high-strength polyphenylene sulfide composite material.
[0021] Preferably, the twin-screw extruder described in step 2 is set to a temperature of 230-250°C in zone 2, 260-280°C in zone 3, 280-290°C in zone 4, 290-300°C in zone 5, 300-310°C in zone 6, 300-310°C in zone 7, 300-310°C in zone 8, 300-310°C in zone 9, 280-290°C in zone 10, 280-290°C in zone 11, 280-290°C in zone 12, 300-310°C in zone 13, and 310-320°C in die head.
[0022] Preferably, step 3 is electron beam irradiation treatment with an irradiation dose of 100-200 kGy.
[0023] Compared with the prior art, the present invention has the following characteristics: (1) In the present invention, reactive silicone oil is added and electron beam irradiation is performed to cause a grafting reaction with PPS, thereby improving the long-term hydrophobicity of the composite material and significantly reducing the wetting of the surface by the electrolyte, thereby improving the CTI value of the composite material; (2) Adding silane coupling agent to modify montmorillonite, after irradiation grafting, montmorillonite can better combine with PPS. Montmorillonite has a lamellar structure and can cover PPS more effectively. It cooperates with glass fiber and carbonization inhibitor to reduce the generation of pathways. At the same time, some reactive silicone oil is adsorbed on montmorillonite to improve hydrophobicity, thereby improving the CTI value of the composite material. (3) The combined use of reactive silicone oil and silane coupling agent modified montmorillonite can effectively reduce the amount of carbonization inhibitor added and reduce the impact of carbonization inhibitor on the performance of composite materials. At the same time, reactive silicone oil can improve the hydrophobicity of carbonization inhibitor, thereby better improving the CTI value of composite materials. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with specific examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. All raw materials used in the following examples and comparative examples are commercially available unless otherwise specified.
[0025] The raw material information and auxiliary agent information used in the examples and comparative examples are as follows: PPS: 3450, Xinhecheng Glass fiber: ECS309A-3-H, CPIC Silane coupling agent: KH-560 Montmorillonite: Sodium Montmorillonite, Guangzhou Xijia Chemical Epoxy silicone oil, amino silicone oil: Dow Silicone: GM-100 Chengdu Chenguang Magnesium hydroxide: HT-206 Taixing Ethanol: Commercially available Acetic acid: Commercially available Material characterization method: Tensile properties are in accordance with ISO 527, the sample size is 170mm×10mm×4mm, and the tensile speed is 10mm / min; Flexural properties are in accordance with ISO 178, the sample size is 80mm×10mm×4mm, the bending speed is 2mm / min, and the span is 64mm; CTI is tested in accordance with GB / T 4207 standard.
[0026] First, weigh KH-560 and montmorillonite at a mass ratio of 4:5 for use, first add KH-560 to an ethanol solution prepared with acetic acid to a pH of 4, hydrolyze for 4 hours, then add montmorillonite to the above mixture and reflux at 70°C for 24 hours. Then dilute the product with anhydrous ethanol, wash, and filter to obtain modified montmorillonite.
[0027] Then weigh the corresponding materials according to the formula in Table 1, mix the raw materials except glass fiber and magnesium hydroxide evenly, and then put them into the main feed weight loss scale, put the glass fiber into the first side feed weight loss scale, put the magnesium hydroxide into the second weight loss scale, and then melt blend, extruder temperature: 230℃ in the second zone, 280℃ in the third zone, 280℃ in the fourth zone, 290℃ in the fifth zone, 310℃ in the sixth zone, 310℃ in the seventh zone, 310℃ in the eighth zone, 300℃ in the ninth zone, 280℃ in the tenth zone, 280℃ in the eleventh zone, 2290℃ in the twelfth zone, 310℃ in the thirteenth zone, 320℃ in the die, and then draw the strands and air cool the pellets to obtain glass fiber reinforced PPS composite material particles. The obtained particles are then irradiated with a 5MeV electron accelerator, and the irradiation dose is shown in Table 1.
[0028] formula Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 3450 28 28 25 31 23 28 39 31 36 24 28 28 309A 30 30 30 30 40 30 30 30 30 30 30 30 Magnesium hydroxide 30 30 30 30 25 30 30 30 30 42 30 30 KH-560 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Modified montmorillonite 8 8 10 6 8 8 0 8 0 0 8 8 Epoxy silicone oil 0 0 0 0 0 3 0 0 0 0 0 0 Amino silicone oil 3 3 4 2 3 0 0 0 3 3 3 3 Silicone 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Irradiation dose kGy 100 200 200 200 200 200 0 200 200 200 300 50 The performance test results of Examples 1-6 and Comparative Examples 1-6 are shown in Table 2.
[0029] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Tensile strength / MPa 134.2 141.6 139.8 133.6 152.6 138.1 123.2 126.4 126.1 111.1 121.7 128.4 Bending strength / MPa 179 191 201 182 210 186.8 146 181 172 145 166 162 Flexural modulus / MPa 21861 23612 24741 22016 25391 22751 18032 21538 19375 19910 22610 19835 CTI / V 600 600 600 600 600 600 425 475 525 600 575 500 From the test results of Examples 1-6 and Comparative Examples 1-6 in Table 2, it can be seen that with the addition of modified montmorillonite and reactive silicone oil, the composite material obtained by melt blending and then irradiation grafting has good mechanical properties and a CTI value of more than 600 V. Preferably, 6-10 parts of modified montmorillonite, 2-4 parts of amino silicone oil, and an irradiation dose of 100-200 kGy.
[0030] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A hydrophobic, high CTI, high-strength polyphenylene sulfide composite material, the raw materials comprising, by weight: Polyphenylene sulfide: 20-50 Glass fiber: 20-50 Coupling agent: 0.2-2 Carbonization inhibitor: 20-40 Modified montmorillonite: 5-12 Reactive silicone oil: 0.2-6 Lubricant: 0.5-2.
2. A hydrophobic high CTI high strength polyphenylene sulfide composite material according to claim 1, characterized in that: The polyphenylene sulfide is a linear polyphenylene sulfide having a melt index of 200-1500 g / 10 min when tested at 316° C. and 5 kg.
3. The hydrophobic high CTI high strength polyphenylene sulfide composite material according to claim 1, characterized in that: The glass fiber is alkali-free chopped glass fiber with a length of 2-6 mm and a diameter of 7-13 μm.
4. The hydrophobic high CTI high strength polyphenylene sulfide composite material according to claim 1, characterized in that: The coupling agent is one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent, or a mixture of several of them.
5. The hydrophobic high CTI high strength polyphenylene sulfide composite material according to claim 1, characterized in that: The carbonization inhibitor is one or a mixture of magnesium hydroxide, aluminum hydroxide, zinc borate and calcium borate.
6. The hydrophobic high CTI high strength polyphenylene sulfide composite material according to claim 1, characterized in that: The modified montmorillonite is sodium-based montmorillonite grafted with a silane coupling agent.
7. The hydrophobic high CTI high strength polyphenylene sulfide composite material according to claim 1, characterized in that: The reactive silicone oil is one of epoxy silicone oil, carboxyl silicone oil and amino silicone oil, or a mixture of several of them.
8. The hydrophobic high CTI high strength polyphenylene sulfide composite material according to claim 1, characterized in that: The lubricant is one of silicone, tetrapentyl stearate and montan wax or a mixture of several of them.
9. A method for preparing a hydrophobic, high CTI, high-strength polyphenylene sulfide composite material according to any one of claims 1 to 8, comprising the following steps: (1) Preparation of modified montmorillonite. Weigh KH-560 and montmorillonite in a mass ratio of 4:5 respectively for use. First, add KH-560 to an ethanol solution prepared with acetic acid to a pH of 4, hydrolyze for 4 hours, and then add montmorillonite to the above mixture and reflux at 70°C for 24 hours. Then dilute the product with anhydrous ethanol, wash, and filter to obtain modified montmorillonite; (2) The modified montmorillonite obtained in step 1 is mixed with polyphenylene sulfide, silane coupling agent, amino silicone oil and silicone, and then put into the main feed weight loss scale of a co-rotating twin-screw extruder with a length-to-diameter ratio of 52:1, the glass fiber is put into the side feed weight loss scale of the sixth section, and the magnesium hydroxide is put into the side feed weight loss scale of the tenth section. The mixture is heated, melted and extruded, and air-cooled and pelletized to obtain a reinforced polyphenylene sulfide composite material; (3) The obtained reinforced polyphenylene sulfide is subjected to electron beam or gamma ray irradiation treatment to obtain a hydrophobic, high CTI, and high-strength polyphenylene sulfide composite material.
10. The method for preparing a hydrophobic, high CTI and high strength polyphenylene sulfide composite material according to claim 9, characterized in that: Step (3) is electron beam irradiation treatment, and the irradiation dose is 100-200 kGy.
Citation Information
Patent Citations
A hydrophobic high CTI polyphenylene sulfide composition, its preparation method and application
CN112457670B
A kind of ultra-high relative tracking index polyphenylene sulfide composite material and preparation method thereof
CN117186643B
High CTI (comparative tracking index) polyphenylene sulfide composition prepared based on multi-dimensional formula design as well as preparation method and application of high CTI polyphenylene sulfide composition
CN117903596A
High-flame-retardant polyphenylene sulfide (PPS) modified polymer and preparation process thereof
CN113480850A
Ultrahigh relative tracking index polyphenylene sulfide composite material and preparation method thereof
CN117186643A
Cited By
High-temperature-resistant PPS (polyphenylene sulfite) and preparation method thereof
CN122356798A